Pengembangan Media Pembelajaran Diorama Tata Surya Pada Mata Pelajaran IPAS Kelas VI - Titik Wahyuningsih; Eka Ramiati; Nurul Fatimah; Kurniyatul Faizah (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2026)
This study aims to develop a solar system diorama as a learning medium for the IPAS subject in grade VI at MINU 1 Purwoharjo. The research was motivated by students’ low motivation and difficulties in understanding abstract concepts of the solar system due to limited interactive learning media. The method employed was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included material and media experts as validators, and 20 sixth-grade students. The validation results indicated that the material expert rated the diorama at 100% feasibility (very feasible), while the media expert rated it at 86.5% (very feasible). Student responses during the trial showed positive results with scores ranging from 76% to 90% (very good category). Effectiveness analysis using the N-Gain test revealed an average score of 0.6048 (medium category) and a learning improvement of 60.48% (fairly effective category). Furthermore, the paired sample t-test yielded a significance value of 0.000 < 0.05, confirming a significant difference between pretest and posttest scores. Therefore, the solar system diorama is considered valid, practical, and effective in enhancing students’ understanding of solar system concepts, while also supporting the implementation of the Merdeka Curriculum through experiential and contextual learning.